Interrater reliability of fitness gram test to be used as a reliable tool for assessing physical fitness for school children in Guwahati urban society of North-East India - Gogoi, Pranjal; Bhattacharyya, Nirmal C. (International Journal of Research in Medical Sciences, 2019)
Background: The assessment of physical fitness using a specific tool has become an important part to find out the fitness level of children and adolescence. Fitness gram is a health-related fitness test that utilizes criterion-referenced standards on health-related components. Through the years research has shown that Fitness gram has become one of the most widely used programs in the United States, though it’s used in India is not popular. Methods: Seventy school students in the age group of 5 to 14 years were included in this study and randomly allocated for physical fitness test where 62 students have completed the test. Two physiotherapists as a rater were allotted and children were tested by them with Fitnessgram test battery in a gap of 1 week. Outcome measures includes Fitness gram test battery. Statistical analysis was done by Cronbach’s Alpha value has been computed for the Interrater reliability. Results: Sixty-two students with both gender (male 56.3% and female 43.7%, age -10.12±2.72) were assessed for physical fitness using Fitness gram test battery. All the test variables showed an excellent reliability (Cronbach’s alpha =0.91-0.95). Conclusions: The Fitness gram test battery has been found to be reliable tool and can be implemented for physical fitness test for the children.